Sleep architecture and quality and pain experience in individuals with persistent low back pain and asymptomatic controls - Xuewen Wang; Jennifer M. C. Vendemia; Erin E. Kishman; John R. Gilliam; Alexandria M. Reynolds; Sheri P. Silfies (PLoS ONE, 2025)
Introduction Both pain and sleep have a broad impact on health and well-being. There is a bi-directional association between pain and sleep, but how sleep and pain are associated chronically remains unclear. This study examined the associations of sleep architecture and quality in relation to pain experience and its impact in individuals with persistent low back pain (pLBP) and asymptomatic controls. Methods Participants included individuals in a current episode of low back pain with symptoms impacting function and persisting greater than three months (pLBP group, n = 20) and asymptomatic controls (control group, n = 19). A home sleep test device (Zmachine® Insight + , General Sleep Corporation) was used for three nights to ecologically assess sleep architecture and quality. Pain, psychosocial factors, and lumbar movement control were evaluated using standard testing. Results The participants were 25.0 ± 4.8 yrs (mean±SD) with similar height, weight, and waist and hip circumferences in the pLBP and control groups. Deep sleep time was shorter (p = 0.034) for the pLBP (1.4 ± 0.4 hr) compared to the control group (1.7 ± 0.3 hr). For the pLBP group, deep sleep time and some sleep quality measures were associated with several pain-related anxiety, daily function, and impact measures independent of total sleep time. Conclusion These results indicate associations of sleep architecture and quality with pain experience in individuals with pLBP. Of all the sleep stages, the deep sleep stage may be more impacted by chronic pain than other stages.